Characterizations of dissimilar refill friction stir spot welding 2219 aluminum alloy joints of unequal thickness. (July 2022) - Zou, Yangfan; Li, Wenya; Yang, Xiawei; Patel, Vivek; Shen, Zhikang; Chu, Qiang; Wang, Feifan; Tang, Huawei; Cui, Fan; Chi, Minliang
Abstract: Refill friction stir spot welding (RFSSW) is a relatively new solid-state spot welding technology. Reliability of the joint is mainly affected by the macroscopic characteristics and microstructure evolution. This method can be applied to weld plates with different thicknesses. However, the temperature distribution, microstructure and mechanical properties of joints with different thicknesses remain unclear. In the present study, 2 mm thick 2219-O aluminum alloy plates were successfully welded to 2219-C10S plates of various thicknesses (4 mm, 10 mm and 14 mm) via the RFSSW method. The effect of lower 2219-C10S plate thickness on the temperature distribution, microstructure, mechanical properties and fracture behavior of RFSSWed joints was evaluated by both experimental and simulation methods. The results indicated that the peak temperature decreased, and the isothermal zone became larger as the thickness of the lower plate increased. A relatively flat hook configuration could be identified in the cross-section of the joint fabricated using a 4 mm thick lower plate, while an upward hook was observed for the joints fabricated using a 10 and 14 mm thick lower plate. Lower plate thickness scarcely affected hardness of the upper plate, but HAZ width of the lower plate becomes narrower with increasing lower sheet thickness. The lap-shear load of the joints fabricated using a lower plate thicknesses of 4, 10 and 14 mm was 7.4 ± 0.3 kN, 6.7 ± 0.2 kN, and 6.4 ± 0.4 kN, respectively, all of them failed as a plug fracture mode. According to the simulation results, tensile and compressive stresses were mainly distributed along the direction of the force on both sides of the weld nugget. While shear stress was primarily distributed in the direction perpendicular to the external force. Furthermore, bending stress was also identified in the joints, which increased with the increase of the lower plate thickness.